Long‐term safety and efficacy of certolizumab pegol in the treatment of Crohn's disease: 7‐year results from the PRECiSE 3 study. Issue 8 (22nd August 2014) - Sandborn, W. J.; Lee, S. D.; Randall, C.; Gutierrez, A.; Schwartz, D. A.; Ambarkhane, S.; Kayhan, C.; Pierre‐Louis, B.; Schreiber, S.; Lichtenstein, G. R.
Summary Background The efficacy and safety of certolizumab pegol (CZP) in moderate‐to‐severe Crohn's disease were demonstrated in two 26‐week double‐blind studies (PRECiSE 1 & 2). Aim To report the safety and efficacy outcomes of long‐term, CZP therapy from PRECiSE 3, in which patients received treatment up to 7 years treatment. Methods Patients completing PRECiSE 1 or 2 were eligible to enter PRECiSE 3 in which they received CZP 400 mg, open‐label, every 4 weeks (without additional induction therapy) for up to 7 years, for up to 91 doses from study start. Safety (adverse events, including infections and malignancies) and efficacy (Harvey–Bradshaw Index, faecal calprotectin, C‐reactive protein) were prospectively monitored. Remission was analysed using observed cases, last observation carried forward imputation and nonresponder imputation. Results A total of 595 patients entered the study; 117 (20%) completed 7 years. Discontinuation rates were 29.2%, 13.6%, 16.1%, 7.9%, 5.0%, 4.5% and 3.9% (years 1–7 respectively). During 1920 patient‐years of exposure to CZP, no new safety signals were observed. Incidence rates (new cases/100 patient‐years) for serious infections and malignant neoplasms were 4.37 and 1.06 respectively. No lymphoproliferative malignancies were reported. Clinical remission rates were ≥68% at each year (observed cases); rates by last observation carried forward and nonresponder imputation were 58% and 45% at year 1, 56% and 26% at year 3 and 55% and 13% at year 7 respectively. Conclusion Certolizumab pegol was well tolerated in the long‐term treatment of Crohn's disease, with sustained remission in some patients continuing in the study for up to 7 years. ClinicalTrials.gov identifier NCT00552058.